Panel Discussion on Artificial Intelligence Theory and Practice: Hard Challenges and Opportunities Ahead - Horvitz, Eric; Getoor, Lise; Guestrin, Carlos; Hendler, James; Konstan, Joseph; Subramanian, Devika; Wellman, Michael; Kautz, Henry (2008)
Microsoft Research Faculty Summit Transcript.